2015
DOI: 10.3390/met6010003
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Behaviors of Ultrafine-Grained ZE41A Magnesium Alloy in DMEM Solution

Abstract: Abstract:The main limitation to the clinical application of magnesium alloys is their too-fast degradation rate in the physiological environment. Bio-corrosion behaviors of the ZE41A magnesium alloy processed by multi-pass equal channel angular pressing (ECAP) were investigated in Dulbecco's Modified Eagle Medium (DMEM) solution, in order to tailor the effect of grain ultrafining on the biodegradation rate of the alloy implant. Hydrogen evolution tests indicated that a large number of ECAP passes decreased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The microstructure produced by MAD processing is more favorable: it is fine grained (~1 µm) and contains more corrosion-resistant particles of the Mg 41 Nd 5 phase, evenly distributed in the matrix. As reported in the literature, the formation of a uniform UFG structure can improve the corrosion resistance of magnesium alloys [25][26][27][28]. In our case, the uniformity of the distribution of the Mg 41 Nd 5 particles did not cause the occurrence of inhomogeneity of corrosion, suggesting that the formation of cathode-anode pairs with the metal matrix was not an issue here [29,30].…”
Section: Discussionsupporting
confidence: 76%
“…The microstructure produced by MAD processing is more favorable: it is fine grained (~1 µm) and contains more corrosion-resistant particles of the Mg 41 Nd 5 phase, evenly distributed in the matrix. As reported in the literature, the formation of a uniform UFG structure can improve the corrosion resistance of magnesium alloys [25][26][27][28]. In our case, the uniformity of the distribution of the Mg 41 Nd 5 particles did not cause the occurrence of inhomogeneity of corrosion, suggesting that the formation of cathode-anode pairs with the metal matrix was not an issue here [29,30].…”
Section: Discussionsupporting
confidence: 76%
“…Low stacking fault energy implies a wide separation of dislocations to cross-slipping. This difficulty interprets the relatively lower recovery rates, which results in lower erosion rates [41][42][43]. Figure 7 shows the variation of weight loss with ECAP passes as a function of slurry velocity.…”
Section: Effect Of Ecap On Erosion-corrosion At Different Test Durationsmentioning
confidence: 99%
“…At low velocities, the erodent is not completely suspended in the fluid; therefore, the erosion is unable to occur. It is recognized that erosion is a function of the fluid velocity (v) and it and be calculated by the nonlinear formula: Erosion = K·(v) n , where K is a constant depends upon particle size and impacting angle, and n is the velocity exponent [41,42]. Comparing the weight losses for pass zero (annealed copper) and four pass ECAP at different velocities it is observed that E-C resistances increased by 0%, 14%, 31.8%, and 13% at 1.4 m/s, 2.7 m/s, 3.8 m/s, and 5.4 m/s, respectively.…”
Section: Effect Of Ecap On Erosion-corrosion At Different Test Durationsmentioning
confidence: 99%
“… Corrosion rate reported in samples of magnesium processed via ECAP [ 52 , 55 , 56 , 57 , 58 , 59 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 69 , 71 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 82 , 83 , 84 , 85 , 86 , 87 ] and HPT [ 19 , 88 , 90 , 91 , 92 , 93 , 94 , 95 , 97 , 98 , 99 , 100 ] plotted as a function of the grain size. …”
Section: Figurementioning
confidence: 99%